Ili ti Bauang Bauang Public Market - Tolentino, Christelle (College of Architecture, University of the Philippines Diliman, 2018)
The drastic decline of Bauang's economy started from the fall of its tourism industry caused by the rise of sea level and the degradation of the shoreline. Since then, agriculture and fish industry has been the only source of income of the locals. Considering the low quality of education and the lack of sufficient livelihood, the locals remain in poverty and this has also led to the increased number of OFWs in the community. The design aims to lift the economy of Bauang through affirming the identity of the place as community of farmers and fishermen.